Structural insights into the electron/proton transfer pathways in the quinol:fumarate reductase from Desulfovibrio gigas. Issue 1 (December 2018) - Guan, Hong-Hsiang; Hsieh, Yin-Cheng; Lin, Pei-Ju; Huang, Yen-Chieh; Yoshimura, Masato; Chen, Li-Ying; Chen, Shao-Kang; Chuankhayan, Phimonphan; Lin, Chien-Chih; Chen, Nai-Chi; Nakagawa, Atsushi; Chan, Sunney; et al.
Abstract The membrane-embedded quinol:fumarate reductase (QFR) in anaerobic bacteria catalyzes the reduction of fumarate to succinate by quinol in the anaerobic respiratory chain. The electron/proton-transfer pathways in QFRs remain controversial. Here we report the crystal structure of QFR from the anaerobic sulphate-reducing bacteriumDesulfovibrio gigas (D .gigas ) at 3.6 Å resolution. The structure of theD .gigas QFR is a homo-dimer, each protomer comprising two hydrophilic subunits, A and B, and one transmembrane subunit C, together with six redox cofactors including twob -hemes. One menaquinone molecule is bound near hemeb L in the hydrophobic subunit C. This location of the menaquinone-binding site differs from the menaquinol-binding cavity proposed previously for QFR fromWolinella succinogenes . The observed bound menaquinone might serve as an additional redox cofactor to mediate the proton-coupled electron transport across the membrane. Armed with these structural insights, we propose electron/proton-transfer pathways in the quinol reduction of fumarate to succinate in theD .gigas QFR.